The Reactions of Common Chemical Fertilizers in An Ultisol and Their Effects on Cowpea Performance - Oyeyiola Yetunde Bunmi; Omueti John Ajayi (JOURNAL OF TROPICAL SOILS, 2019)
Chemical fertilizers (CF) are the major input on arable farms in Nigeria. Current increasing rate of nutrient depletion in CF treated soils calls for the need to study their reactions in soils. To achieve this, three CF based treatments, namely NPK 15:15:15 applied at 40 kg P2O5 ha-1, Urea applied at 20 kg N ha-1  mixed with Single superphosphate at 40 kg P2O5 ha-1, and single superphosphate at 40 kg P2O5 ha-1  mixed with Gliricidia sepium leaves at 20 kg N ha-1  were studied. Sole lime (CaCO3) at 1 Mg ha-1 and a plot that received no amendment were compared. Cowpea was grown for two consecutive cropping seasons in 2012 and 2013 on the treated fields. The results indicated that CF reduced soil pH from initial 4.8 to 4.0. The NPK 15:15:15 fertilizer was the most severe of the CF tested, removing up to 133% alkalinity from the soil relative to lime. The NPK 15:15:15 reduced calcium saturation (from 25% to 21%) and magnesium saturation (from 12% to 8.3%) and increased acidity saturation (from 53% to 66%) with significant reductions in organic carbon content (from 13.2 g kg-1 to 11.0 g kg-1). Precaution including co-application of CF with organic materials such as Gliricidia sepium leaves can benefit for the soils.